Oxytocin enhances the pain-relieving effects of social support in romantic couples - Kreuder, Ann-Kathrin; Wassermann, Lea; Wollseifer, Michael; Ditzen, Beate; Eckstein, Monika; Stoffel-Wagner, Birgit; Hennig, Jürgen; Hurlemann, René; Scheele, Dirk (Human brain mapping, 2019)
Social support plays a vital role in physical and mental well-being. The neuropeptide hormone oxytocin (OXT) has been implicated in modulating pair-bonding and affiliative behaviors, but whether OXT contributes to the analgesic effects of a romantic partner's touch remains elusive. In the present randomized placebo-controlled, between-group, functional magnetic resonance imaging study involving 194 healthy volunteers (97 heterosexual couples), we tested the effects of intranasal OXT (24 IU) on handholding as a common mode of expressing emotional support in romantic couples. We scanned the subjects while brief electric shocks were administered. The subjects assumed that they received social support from either their romantic partner or an unfamiliar person. Unbeknown to the subject, in the partner and stranger support conditions, the same male experimenter always held the subject's left hand. Partner support was most effective in reducing the unpleasantness of electric shocks, and OXT further attenuated the unpleasantness across conditions. On the neural level, OXT significantly augmented the beneficial effects of partner support, as evidenced by a stronger decrease of neural responses to shocks in the anterior insula (AI), a stronger activity increase in the middle frontal gyrus (MFG), and a strengthened functional coupling between the AI and MFG. Our results support the notion that OXT specifically modulates the beneficial effects of social support in romantic couples by concomitantly reducing pain-associated activity and increasing activity linked to cognitive control and pain inhibition. We hypothesize that impaired OXT signaling may contribute to the experience of a lack of partner support.
First published: 28 August 2018
Gesehen am 03.07.2019